Metronidazole release using natural rubber latex as matrix - Herculano, Rondinelli Donizetti [UNESP]; Guimarães, Sérgio Augusto Catanzaro; Belmonte, Gustavo Campos; Duarte, Marco Antonio Hungaro; Oliveira Júnior, Osvaldo Novais de; Kinoshita, Angela; Graeff, Carlos Frederico de Oliveira [UNESP] (ABM, ABC, ABPol, 2010)
Natural Rubber Latex (NRL) can be used successfully in controlled release drug delivery due to their excellent matrix forming properties. Recently, NRL has shown to stimulate angiogenesis, cellular adhesion and the formation of extracellular matrix, promoting the replacement and regeneration of tissue. A dermatological delivery system comprising a topically acceptable, inert support impregnated with a metronidazole (MET) solution was developed. MET 2-(2- methyl- 5-nitro- 1H- imidazol- 1-yl) ethanol, has been widely used for the treatment of protozoa and anaerobic bacterial infections. MET is a nitroimidazole anti-infective medication used mainly in the treatment of infections caused by susceptible organisms, particularly anaerobic bacteria and protozoa. In a previous study, we have tested NRL as an occlusive membrane for GBR with promising results. One possible way to decrease the inflammatory process, it was incorporated the MET in NRL. MET was incorporated into the NRL, by mixing it in solution for in vitro protein delivery experiments. The solutions of latex and MET were polymerized at different temperatures, from -100 to 40 °C, in order to control the membrane morphology. SEM microscopy analysis showed that the number, size and distribution of pores in NRL membranes varied depending on polymerization temperature, as well as its overall morphology. Results demonstrated that the best drug-delivery system was the membrane polymerized at -100 °C, which does release 77,1% of its MET content for up 310 hours.
Keywords: biomaterials; latex membrane; metronidazole; drug delivery system